A Note on Pata-Type Cyclic Contractions - Kadelburg, Zoran; Radenović, Stojan (Sarajevo Journal of Mathematics, 2024)
Several fixed point results are obtained for cyclic mappings satisfying contractive conditions of Pata-type. Some of them improve existing results in the literature. An example shows a possible usage of the obtained results. 2010 Mathematics Subject Classification. Primary 47H10; Secondary 47H09.